Теоретичні й практичні аспекти моніторінгу фінансової звітності як напряму виявлення загроз фінансовій безпеці підприємства в умовах воєнного стану - Дубинська Олена; Dubinska Olena; Dubinszka O. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Резюме. Воєнний стан на території України й повномасштабні бойові дії на значній території держави стали викликом для більшості сфер і галузей національної економіки. Уряд усвідомлює складність становища українських підприємств в умовах воєнного стану й законодавчо закріпив послаблення в питанні подання, оприлюднення й аудиту фінансової звітності. Проте аналіз наукової літератури з питань забезпечення належного рівня фінансової безпеки підприємства дає змогу визначити, що відсутність постійного аудиту й своєчасного виявлення загроз фінансовій безпеці може стати причиною втрати фінансової рівноваги на підприємстві. Тому питання аудиту як напряму виявлення загроз фінансовій безпеці підприємства в умовах воєнного стану набуває надзвичайної значимості. Враховуючи актуальність проблеми, метою дослідження є конкретизація теоретичних положень та розробка практичних рекомендації щодо проведення моніторингу фінансової звітності для виявлення загроз фінансовій безпеці підприємства в умовах воєнного стану. В процесі аналізу одним із ключових питань постає розуміння сутності загрози фінансовій безпеці підприємства. В роботі окреслено джерела виникнення відповідних загроз й визначено можливі напрями їх ранньої діагностики. В процесі досягнення мети дослідження встановлено, що на період воєнного стану, коли підприємства не мають можливості проводити повноцінний аудит фінансової звітності, раціонально зосередити увагу на здійсненні внутрішнього моніторингу фінансового стану, який дозволить своєчасно виявляти загрози й створить підґрунтя для ухвалення управлінських рішень, спрямованих на забезпечення достатнього рівня фінансової безпеки. Також розроблено й обґрунтовано принципи, на яких повинна будуватися система внутрішнього фінансового моніторингу. Доведено, що в умовах воєнного стану, коли є обмеження щодо подання й оприлюднення фінансової звітності, підприємства все одно зацікавлені в аналізі фінансового стану й визначенні потенційних загроз фінансовій безпеці.

Az ukrajnai hadiállapot és a teljes körű katonai műveletek az ország nagy részén kihívást jelentenek a nemzetgazdaság legtöbb ágazata számára. A kormány tudatában van annak, hogy a hadiállapot alatt álló ukrán vállalkozások helyzete nehézségekkel küzd, ezért enyhítéseket vezetett be a pénzügyi kimutatások benyújtására, közzétételére és ellenőrzésére vonatkozóan. A vállalkozás megfelelő szintű pénzügyi biztonságának biztosításáról szóló tudományos szakirodalom elemzése azonban azt mutatja, hogy a rendszeres könyvvizsgálat és a pénzügyi biztonságot fenyegető veszélyek időben történő felderítésének hiánya a vállalkozás pénzügyi egyensúlyának elvesztéséhez vezethet. Ezért az auditálás kérdése, mint a vállalkozás pénzügyi biztonságát fenyegető veszélyek felismerésének eszköze, a háburú idejében kiemelkedő jelentőséggel bír. Tekintettel a probléma relevanciájára, a tanulmány célja az elméleti elemek pontosítása és gyakorlati ajánlások kidolgozása a pénzügyi kimutatások ellenőrzése kapcsán, azonosítva a hadiállapot alatt álló vállalkozás pénzügyi biztonságát fenyegető veszélyeket. Az elemzés során az egyik legfontosabb kérdés a vállalkozás pénzügyi biztonságát fenyegető veszély jellegének megértése. A kutatás felvázolja a releváns fenyegetések forrásait és meghatározza a korai diagnisztizálás lehetséges területeit. A kutatási cél elérése során a szerző megállapította, hogy a hadiállapot időszakában, amikor a vállalkozások nem képesek a pénzügyi kimutatások teljes körű könyvvizsgálatára, ésszerű a pénzügyi helyzet belső ellenőrzésére összpontosítani, ami lehetővé teszi a fenyegetések időben történő felismerését, és megteremti az alapot a megfelelő szintű pénzügyi biztonságot célzó vezetői döntések meghozatalához. Ugyancsak sor került a belső pénzügyi monitoring rendszerének alapjául szolgáló elvek kidolgozására és megalapozására. Bebizonyosodott, hogy a hadiállapotra vonatkozó törvények értelmében, amikor a pénzügyi kimutatások benyújtására és közzétételére korlátozások vannak érvényben, a vállalkozások továbbra is érdekeltek pénzügyi helyzetük elemzésében és a pénzügyi biztonságot fenyegető potenciális veszélyek azonosításában.

Abstract. Martial law on the territory of Ukraine and full-scale hostilities on a significant territory of the state have become a challenge for most spheres and branches of the national economy. The government is aware of the complexity of the situation of Ukrainian enterprises in the conditions of martial law and legislated relaxations in the issue of submission, publication and audit of financial statements. However, the analysis of the scientific literature on the issue of ensuring the appropriate level of financial security of the enterprise makes it possible to determine that the lack of constant audit and timely identification of threats to financial security can cause the loss of financial balance at the enterprise. Therefore, the issue of auditing financial statements as a means of identifying threats to the financial security of an enterprise in the conditions of martial law is becoming extremely urgent. Taking into account the relevance of the research area, the purpose of the research is the specification of theoretical provisions and the development of practical recommendations regarding the implementation of the audit of financial statements as a way of identifying threats to the financial security of the enterprise in the conditions of martial law. In the process of analyzing financial security, one of the key issues is understanding the essence of the threat to the company's financial security. The paper identifies the sources of the occurrence of the specified threats and outlines the possible directions for early diagnosis of these threats. Also, in the work, in the process of achieving the goal of the research, it was established that during the period of martial law, when enterprises do not have the opportunity to conduct a full-fledged audit of financial statements, it is rational to focus attention on conducting internal monitoring of the financial state, which will allow timely detection of threats to financial security and create a basis for making management decisions aimed at ensuring a sufficient level of financial security. The work also developed and substantiated the principles on which the system of internal financial monitoring should be built. It has been proven that during the period of martial law, when there are restrictions on the submission and publication of financial statements, enterprises are still interested in analyzing the financial situation and identifying potential threats to financial security.
A pénzügyi beszámoló könzvvizsgálatának elméleti és gyakorlati aspektusai, mint a hadiállapot idejében működő vállalatok pénzügyi biztonságát fenyegető veszélyeinek azonosítási iránya
Theoretical and practical aspects of the audit of financial statements as a way identifying threats to the financial security of the enterprise in the conditions of martial law
https://aab-economics.kmf.uz.ua/aabe/issue/view/4
Keywords: аудит; моніторинг; фінансова безпека; загроза фінансовій безпеці; фінансовий стан; фінансова звітність